Digital Empowerment: Ensuring Legal Protections for Online Arisan Engagements - Negara, Dharma Setiawan; Darmawan, Didit (Metromedia, 2023)
Digitalization changes transactions that initially had to meet without physical meetings. One example is online social gathering which is the result of this development, where the agreement and implementation of the social gathering is carried out via social media platforms. At the same time, this agreement also creates an agreement, so that online or virtual social gatherings become the basis for its implementation. Even though this transaction has provided convenience, it will also pose risks for participants in the virtual social gathering. This research aims to find the characteristics of online arisan agreements which are based on positive Indonesian legal rules and identify legal protection efforts for online arisan members. The data was analyzed qualitatively after going through the stages of examination, reconstruction and data systematization. The study results indicate online social gathering agreements exhibit a number of distinguishable features. To begin with, these agreements made online can be categorized as anonymous agreements, standard agreements, and reciprocal agreements. This indicates the various forms of online social gathering agreements that exist. Second, the requirements for participating in online social gatherings are usually broadcast via social media, and communication occurs online or virtually, without direct face-to-face meetings. The existing online social gathering agreement is carried out virtually, based on the level of trust that is built between the owner/organizer as well as the participants in the social gathering. Third, from a legal perspective, Agreements related to online social gatherings are regarded as electronic transactions as per the electronic information and transactions law (UU ITE). This indicates that electronic rules apply to this agreement. Fourth, proof of The agreement for the online social gathering can be located using the withdrawal serial number provided by the owner or organizer to the members at the beginning of the event. This is concrete evidence of the agreement that has been made. Apart from that, legal protection for the public, especially online social gathering members, is divided into two. First, preventive legal protection or in other words efforts to prevent legal problems before they occur, which have been regulated in the laws and regulations related to online social gatherings, namely in the Civil Code (KUHPerdata), the ITE Law, and online social gathering agreements. have been made by the parties themselves. This aims to prevent violations and conflicts in online social gathering agreements. Second, Stringent legal safeguarding encompasses penalties, including monetary fines and restitution given in cases of violation of online social gathering agreements. For this reason, legal remedies are available to maintain the security and validity of online social gathering agreements in accordance with Indonesian law.